Fundamentalizm muzułmański jako ruch społeczny (Świat Idei i Polityki, 2006)
Muslim fundamentalism is not only a religious but also a social and political phenomenon. Political science considers it both a political ideology and a social movement. Since we have been observing an increase in its popularity for a few dozen years, it is worth considering what makes a lot of Muslims follow this fundamentalistic ideology. The author tries to answer the questions: who an average fundamentalist is, what education he obtained and what attracts him to the fundamentalistic movement. The author also describes the social basis of fundamentalism, which will permit us to find why this ideology is so popular. The author considers poverty as a catalysing factor but he also points to transformations in Muslim societies concerning modernity, such as globalisation, political centralisation, urbanisation, massmedia widespreading, or migrations. Neither does he miss antiAmericanism as an important mobilising factor. The other part of this paper concerns the so called "Muslim terrorism" and its relationship with fundamentalism. The author takes note of the necessity to differentiate between the both concepts and presents the two streams of fundamentalism: terrorist (salafijja dżihadu) and "peaceful".